Reliability and Clinical Utility of the CARDS Classification for Degenerative Spondylolisthesis. Issue 1 (February 2018) - Sobol, Garret L.; Hilibrand, Alan; Davis, Ashley; Millhouse, Paul; Koerner, John; Kepler, Christopher; Schroeder, Gregory D.; Krystal, Jonathan D.; Olsson, Erik C.; Rihn, Jeffrey; Anderson, David Greg; Vaccaro, Alexander; et al.
Abstract : Study Design: Retrospective cohort study. Objective: The objective of this study is to determine the reliability and clinical utility of the of the proposed CARDS classification for degenerative spondylolisthesis. Background: The Clinical and Radiographic Degenerative Spondylolisthesis (CARDS) classification system was recently proposed as an alternative to the Meyerding system for classifying degenerative spondylolisthesis (DS). Unlike Meyerding, CARDS considers other relevant radiographic findings such as disk space collapse and segmental kyphosis to stratify DS into 4 radiographically discreet types. Currently, no studies have been conducted to assess the clinical utility of the CARDS system. Methods: A total of 78 consecutive surgical patients with L4-L5 DS were rated as CARDS types A through D and Fleiss' κ for interobserver agreement was calculated. Then, demographics as well as preoperative and postoperative outcome scores (ODI, SF-12 mental and physical, VAS) were collected. The Kruskal-Wallis test was used to detect significant differences amongst CARDS types. An unpaired t test was used to compare individual CARDS types with all other subtypes combined. Results: Grading showed: 4 type A, 19 type B, 45 type C, and 8 type D ( k =0.63). There was a statistically significant difference in preoperative back pain ( P =0.046) between groups. CARDS type D had the highest mean back pain scores (8.8) of all subtypes which was significantly higher than mean back pain for all other subtypes combined ( P =0.016). CARDS D showed the largest degree of improvement in all outcome measures. There was a trend towards an increased improvement in ODI ( P =0.074) and SF-12 MCS ( P =0.095) in the CARDS D subtype relative to the rest of the cohort. Conclusions: The CARDS classification system represents a reliable method for classifying cases of DS. Our results indicate that kyphotic segmental alignment (CARDS D) may be a less common, yet clinically distinct subset of DS characterized by worse preoperative back pain. CARDS type D cases may also show a greater degree of improvement in multiple outcome measures following surgical intervention.